Trends in developments in gas-shielded arc welding equipment in Japan - Tomoyuki Ueyama (Автоматическая сварка, 2013)
In the welding field in Japan, new technologies and processes have been developed one after another in response to the improvement in materials and the changes in the market needs, which have remarkably been contributing to rationalization and cost reduction in various industries. Taking into account the abovementioned technological trends, this paper provides an overview of the present situation of technological developments in terms of gas shielded arc welding equipment.